Blockchain‐Enabled Car Sharing: Enhancing Reliability and Vehicle History Management - Chen Ben Tolila; Yarden Hovav; Kiril Danilchenko; Hadassa Daltrophe (Engineering Reports)
ABSTRACT The rising expenses associated with car ownership have driven individuals to seek more affordable alternatives, such as car rentals. However, conventional car rental services often come with high costs due to leasing companies' overhead expenses. Consequently, car sharing has emerged as a popular and cost‐effective solution that reduces expenses and promotes eco‐friendliness by reducing the number of vehicles on the roads. Nonetheless, centralization and reliability remain persistent challenges in car‐sharing implementation. To address these issues, we propose a decentralized crowd car sharing and renting platform called CROWDCARLINK, leveraging blockchain technology's power. This innovative platform enables individuals and leasing companies to rent vehicles while securely recording each car's maintenance and lease history on the blockchain. Within CROWDCARLINK, garages are pivotal contributors, adding vehicle information in a reliable and immutable manner. By utilizing blockchain technology, our platform ensures transparency and fosters trust, effectively overcoming the limitations imposed by centralization. Our architectural design incorporates smart contracts, which help streamline processes and facilitate seamless transactions within the platform. To demonstrate the feasibility of our approach, we have developed a prototype utilizing a private Ethereum blockchain with Proof of Authority (PoA) consensus. We believe that the architectural design and the practical solution presented here will play an integral role in shaping the future of smart transportation. Our platform aims to benefit individuals and the environment by offering a cost‐effective and efficient solution, paving the way for a more sustainable and advanced transportation ecosystem.